Hubungan Tingkat Aktivitas Fisik dan Lama Waktu Kerja Terhadap Siklus Menstruasi Pada Pekerja Wanita - Lubis, Nur Azizah; Sihombing, Juliana sion; Siahaan, May Frinsiska; Dewi, Nina Artika; Herawati, Nurul (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
A characteristic of a woman entering adulthood is menstruation. Menstrual cycles disorder can be influenced by several factors such as age, body weight, physical activity, stress levels, genetics and nutrition. Physical activity levels and length of working hours that trigger stress can affect the menstrual cycle. The purpose of this research knowed the relationship between physical activity levels and length of working hours in menstrual cycle for female workers. This research design uses a cross sectional approach. The population is all female workers of childbearing age who work in Kenangan Village, Deli Serdang Regency. The total sample was 72 working female respondents of childbearing age who were taken using a purposive sampling technique. The results showed that the majority of physical activity level was moderate and has menstrual cycle disorders (36.11%), and length of working hours is more than 8 hours also has the most menstrual cycle disorders (40.27%). The chi-square test of physical activity level with menstrual cycle disorders was shown with p-value of 0,00059 (α < 0.05) and the length of working hours with the menstrual cycle disorder resulted in p-value of 0,00057 (α < 0.05). There is a relationship between physical activity levels and length of working hours in menstrual cycle for female workers.